Poplar leaf rust reduces dry mass accumulation and internal nitrogen recycling more markedly under low soil nitrogen availability, and decreases growth in the following spring - Gortari, Fermín (2019)
Rust is one of the most important biotic stress factors that affect poplars. The aims of this work were: (i) to analyze the changes in growth and nitrogen (N) accumulation in Populus deltoides W. Bartram ex Marshall plants infected with rust (Melampsora medusae Thümen.) and to determine how internal N stores are affected by the disease, in plants growing under two N availabilities in the soil; and (ii) to evaluate the impact of rust in the early sprout in the following growing season and the cumulative effect of the disease after repeated infections. Two clones with different susceptibility to rust were analyzed. At leaf level, rust reduced gas exchange capacity, water conductance in liquid phase and photosynthetic rate in both clones. At plant level, rust reduced plant growth, accelerated leaf senescence and abscission occurred with a higher concentration of leaf N. Even though N concentration in stems and roots were not significantly reduced by rust, total N accumulation in perennial tissues was reduced in infected plants. The vigor of the early sprout of plants infected by rust in the previous season was lower than that of non-infected plants. Therefore, rust affects plant growth by reducing the photosynthetic capacity and leaf area duration, and by decreasing internal nutrient recycling. As nutrient reserves in perennial tissues are lower, rust infection reduces not only the growth of the current season, but also has a cumulative effect on the following years. The reduction of growth was similar in both clones. High availability of N in the soil had no effect on leaf physiology but increased plant growth, delayed leaf senescence and abscission, and increased total N accumulation. If fertilization increases plant growth (stem and root dry mass) it can mitigate the negative effect of the pathogen in the reduction of nutrient storages and future growth.